QUALITY OF WORK LIFE: PERCEPTION OF COLLEGE TEACHERS WITH SPECIAL REFERENCE TO SELF FINANCE COLLEGES AT PERAMBALUR DISTRICT - Selvan, Kalai; ANANDAN, MR; Vijayalakshmi, MRS Dr. (IJRDO- Journal of Educational Research, 2018)
Quality of Work Life (QWL) has been defined as “The quality of relationship between the employees and the total working environment”. QWL is concerned with the overall climate of work and the impact on work and people as well as on organization effectiveness. Quality is no more a specialized word but has become a necessary and must for the best survival. In this era, quality of human inputs is the greatest asset to any organization. Maintaining the quality of such human inputs rises from maintaining the quality of work life perfectly. Rise in the quality of work life would help employees’ well being there by the well being of the whole organization. This research is an attempt to study the quality of work life of college teachers. Legislation enacted in early 20th century to protect employees from job-injury and to eliminate hazardous working conditions, followed by the unionization movement in the 1930 and 1940s were the initial steps. Emphasis was given to job security, due to process at the work place and economic gains for the workers. The 1950s and the 1960s saw the development of different theories by psychologists proposing a “positive relationship between morale and productivity”, and the possibility that improved human relations would lead to the enhancement of both. Attempts at reform to acquire equal employment opportunity and job enrichment schemes also were introduced. Finally, in the 1970s the ideal of QWL was conceived which, according to Walton, is broader than these earlier developments and is something that must include ‘ the values that were at the heart of these earlier reform movements’ and ‘human needs and aspirations’.